2010
DOI: 10.1016/j.jasms.2010.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Old acid, new chemistry. Negative metal anions generated from alkali metal oxalates and others

Abstract: A brief search in Sci Finder for oxalic acid and oxalates will reward the researcher with a staggering 129,280 hits. However, the generation of alkali metal and silver anions via collision-induced dissociation of the metal oxalate anion has not been previously been reported, though Tian and coworkers recently investigated the dissociation of lithium oxalate [18]. The exothermic decomposition of alkali metal oxalate anion to carbon dioxide in the collision cell of a triple quadrupole mass spectrometer leaves no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
14
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 27 publications
(26 reference statements)
1
14
0
Order By: Relevance
“…We have been investigating a procedure to convert certain metal ions from their +1 oxidation state into anions by collision‐induced dissociation (CID) of the anions of metal dicarboxylic acid salts for some time 4. The formation of metal anions from the anions of oxalate salts has been independently communicated recently by the Mayer group 5. However, no details were provided about the dissociation mechanism.…”
mentioning
confidence: 99%
“…We have been investigating a procedure to convert certain metal ions from their +1 oxidation state into anions by collision‐induced dissociation (CID) of the anions of metal dicarboxylic acid salts for some time 4. The formation of metal anions from the anions of oxalate salts has been independently communicated recently by the Mayer group 5. However, no details were provided about the dissociation mechanism.…”
mentioning
confidence: 99%
“…[4] The formation of metal anions from the anions of oxalate salts has been independently communicated recently by the Mayer group. [5] However, no details were provided about the dissociation mechanism. In addition to oxalates, we have observed several other anions of dicarboxylic acid salts producing metal anions as dissociation products.…”
mentioning
confidence: 99%
“…CO 2 is another small molecule with negative EA. The utility of CO 2 as a leaving group was noted by Curtis et al after observing the decomposition of metal–oxalate complexes in the collision cell of a triple quadrupole mass spectrometer to produce M − , where M = Na, K and Ag . The process can be generalized as follows: normalMnormalCnormalO22¯normalM¯prefix+0.25em2normalCnormalO2 where (CO 2 ) 2 represents the oxalate dianion and M is the metal center.…”
Section: Introductionmentioning
confidence: 99%
“…The process can be generalized as follows: normalMnormalCnormalO22¯normalM¯prefix+0.25em2normalCnormalO2 where (CO 2 ) 2 represents the oxalate dianion and M is the metal center. It was theorized by Curtis et al that the high production of AMAs is enabled largely via the negative electron affinity of CO 2 (−0.6 eV), but is also affected by the electron affinity of the metal, the size of the metal and the strength of the bond between the carbon and metal within the complex . Attygale and co‐workers found that other dicarboxylic acid salts such as maleate, fumarate and succinate could also be used …”
Section: Introductionmentioning
confidence: 99%